Local Life Circumstances and Offending Specialization/Versatility : Comparing Opportunity and Propensity Models - McGloin, Jean Marie; Sullivan, Christopher J.; Piquero, Alex R.; Pratt, Travis C. (Journal of research in crime and delinquency, 2007)
Research has consistently indicated that most offenders demonstrate diversity over the life course. Even so, recent work suggests that offenders tend to illustrate specialization in the short-term, though this specialization diminishes as the "time window" for examining an offending career increases. To examine why this pattern emerges, the authors investigate the extent to which opportunity structures, as defined by local life circumstances, predict offense specialization/diversity relative to individuals' enduring propensities to offend. The results suggest that both individual-level propensity, as well as changes in local life circumstances e.g., employment, marriage, drug and alcohol use, impact patterns of offense specialization/versatility in the short term. The implications of these results lot life-course theories of crime, with a particular focus on integrating opportunity and propensity models of criminal behavior, are discussed. ABSTRACT FROM AUTHOR